CARBONATITE-LIKE DYKES FROM THE EASTERN HIMALAYAN SYNTAXIS: GEOCHEMICAL, ISOTOPIC, AND PETROGENETIC EVIDENCE FOR MELTING OF METASEDIMENTARY CARBONATE ROCKS WITHIN THE OROGENIC CRUST - Liu Y.; Berner Z.; Massonne H.-J.; Zhong D. (My University, 2006)
Within the eastern Himalayan syntaxis, carbonatite-like dykes occur in granulite facies gneisses of the Greater Himalayan Crystallines. Most dykes are dolomitic and are associated with scapolite-bearing hornblendite and glimmerite, which are separated from the country rocks by a selvage of altered rocks containing minerals such as diopside, tremolite, K-feldspar, albite, and calcite. Only a few dykes are calcitic with alteration halos containing wollastonite, calcite, anorthite, diopside, and scapolite. Dolomitic dykes as wide as several tens of metres contain irregular xenoliths of granulitic gneiss. Geochemically, the carbonatite-like dykes differ significantly from mantle-derived carbonatites. The dyke rocks are poor in REEs, Ba, Sr, U, Th, Nb, F and P. Their 87Sr/86Sr, 143Nd/ 144Nd, δ18O (relative to V-SMOW) and δ13C (relative to V-PDB) values range from 0.709 to 0.712, 0.5117 to 0.5121, +8 to +24.4‰, and +0.80 to +3.55‰, respectively. These values are similar to those for most sedimentary carbonates suggesting that the carbonatite-like dykes were formed as melts from sedimentary carbonates at crustal levels. Structural analysis has shown that the Greater Himalayan Crystallines were extruded from beneath southern Tibet via ductile channel flow to overlie the limestone/marble-bearing Lesser Himalayan Crystallines. Fluxing of limestones below the Greater Himalayan Crystallines was probably triggered by the overlying Greater Himalayan Crystallines. K-Ar and Ar-Ar geochronology data obtained on amphibole and mica from the carbonate dykes indicate this event occurred during the late Neogene. © 2004 Elsevier Ltd. All rights reserved.
Keywords: CARBONATE; CARBONATITE; DYKES; EASTERN HIMALAYAN SYNTAXIS; ND ISOTOPES; SR ISOTOPES; STABLE ISOTOPES; TRACE ELEMENT CHARACTERISTICS; Neogene; Cenozoic::Neogene; Кайнозой::Неоген